2012
DOI: 10.1128/aem.02385-12
|View full text |Cite
|
Sign up to set email alerts
|

Phe317 Is Essential for Rubber Oxygenase RoxA Activity

Abstract: RoxA is an extracellular c-type diheme cytochrome secreted by Xanthomonas sp. strain 35Y during growth on rubber. RoxA cleaves poly(cis-1,4-isoprene) to 12-oxo-4,8-dimethyltrideca-4,8-diene-1-al (ODTD). Analysis of the RoxA structure revealed that Phe317 is located in close proximity (Ϸ5 Å) to the N-terminal heme that presumably represents the active site. To find evidence of whether Phe317 is important for catalysis, we changed it to tyrosine, tryptophan, leucine, histidine, or alanine. All five RoxA muteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 26 publications
(31 reference statements)
0
47
0
Order By: Relevance
“…The approach to integrate an inducible roxA Xsp gene into a ΔroxA background of Xanthomonas sp. strain 35Y had been previously used successfully for RoxA Xsp expression (11). When we cultivated a clone of the constructed ΔroxA Xanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach to integrate an inducible roxA Xsp gene into a ΔroxA background of Xanthomonas sp. strain 35Y had been previously used successfully for RoxA Xsp expression (11). When we cultivated a clone of the constructed ΔroxA Xanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to express roxB Xsp in Escherichia coli were not successful (not shown). The growth-inhibitory effect of plasmid-derived expression of roxA in E. coli has been described previously (11,28). We therefore integrated roxB Xsp under the control of an L-rhamnose-inducible promoter into the genome of a ΔroxA background of Xanthomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RoxA was purified from a ⌬roxA Xanthomonas sp. with chromosomally integrated roxA plasmid (pNH1::roxA) under rhamnose control as described previously (12,21). Lcp with the replacement of the TAT sequence by a Strep-tag was purified by using E. coli JM109 harboring p4782.1::lcp (volume, 4.8 liters) grown at 22°C for 20 h. The cells were harvested and resuspended in buffer A (1 ml buffer A/g cells, 100 mM potassium phosphate buffer [KPP], pH 7.7, 150 mM sodium chloride).…”
Section: Methodsmentioning
confidence: 99%
“…strain 35Y (9). Biochemical and biophysical investigation revealed that RoxA is an extracellular dioxygenase with two covalently attached heme groups (10,11) and is structurally but not functionally related to cytochrome c peroxidases (12,13). RoxA cleaves poly(cis-1,4-isoprene) to 12-oxo-4,8-dimethyltrideca-4,8-diene-1-al (ODTD; C 15 -tri-isoprenoid) as a main end product.…”
mentioning
confidence: 99%